Rashda : the birth and growth of an Egyptian oasis village - Kato, Hiroshi. (Islamic Area Studies, 2016)
Rashda:The Birth and Growth of an Egyptian Oasis Village is an interdisciplinary study from a multi-perspective, using various kinds of data and information. It offers a comprehensive description of Rashda, a village in Dakhla Oasis in Egypt from its beginning to the present. Key concepts are the uncertainty of the water supply, the dependence on the political regime and the rational behaviour of individuals. The villagers of Rashda have dealt with the difficult natural circumstances by creating the local customs of irrigation and cultivation. The development of village recently depends ever more on the government, as long as large amounts of finance and superior technology are necessary to dig deeper wells to secure water for cultivation.